Analysis of stability in pedestrian downhill roadway at Yindonggou 11th coal mine area: the impact of anchor cable support density - Jinbao, Li (Frontiers in Energy Research, 2024)
The study of cable support density’s impact on the stability of rock in mine roadways is vital for personnel safety, equipment protection, and mining operations continuity. This research examines a typical engineering scenario within the 11th mining area pedestrian downhill roadway of Yindonggou Mine. A numerical model is devised, accounting for post-peak evolution of mechanical parameters in the surrounding rockmass, represented by a plastic shear strain-dependent multi-segment linear function. Factors such as vertical displacement of the roof and floor, cable axial force, and changes in the plastic zone were scrutinized to decipher the influence of anchor cable support density on roadway stability. The study revealed the following results: 1) The displacement pattern of the roadway roof initially decreases at a decreasing rate before stabilizing with an increase in calculation time step. However, the floor displacement increases first at a diminishing rate before achieving stability with increased calculation time. 2) As a result of the pulling effect caused by deformation and movement of roof’s surrounding rock, the axial force of the anchor cable initially rises with a declining rate before reaching a virtually constant value with increased computation time. 3) Analysis of the vertical displacement field of the model illustrates that with the rise in support density, the maximum displacement of the model’s top plate sinking and bottom plate elevation gradually reduces. 4) With the increment in support density, the number of units showing a plastic shear strain greater than 0.2, 0.1, and 0.05 tends to decrease, indicating increased stability of the roadway. Furthermore, it was observed that the probability of plastic shear yielding at the junction of the roadway floor and side is high while the shoulder of the roadway reflects a lower probability.